Seismic analysis of rigid walls retaining a cross-anisotropic elastic soil layer over bedrock. (April 2018) - Beskou, Niki D.; Papagiannopoulos, George A.; Chassiakos, Athanasios P.
Abstract: The dynamic response of rigid walls retaining a cross-anisotropic elastic soil layer over bedrock to seismic horizontal excitation is determined analytically under conditions of plane strain. The problem of a pair of rigid walls is solved first and the one with a single wall is obtained as a special case for a large separation distance between those walls. Assuming time harmonic motion, expansion of the unknown displacements in Fourier sine and cosine series along the horizontal direction, reduces the system of the two partial differential equations of motion in the frequency domain into a system of two ordinary differential equations, which is easily solved analytically. Thus, one can obtain closed form expressions for the seismic soil pressure, the distance from the base of the point of application of the resultant seismic pressure and the base shear force and bending moment. The above cross-anisotropic solution is first verified by comparing it for the special case of isotropy against existing isotropic solutions. Afterwards parametric studies are conducted in order to assess the effect of cross-anisotropy on the seismic response of the wall-soil system.